Neutrophils Return to Bloodstream Through the Brain Blood Vessel After Crosstalk With Microglia During LPS-Induced Neuroinflammation - Kim, Yu Rim; Kim, Young Min; Lee, Jaeho; Park, Joohyun; Lee, Jong Eun; Hyun, Young-Min (Frontiers in Cell and Developmental Biology, 2020)
The circulatory neutrophil and brain tissue-resident microglia are two important immune cells involved in neuroinflammation. Since neutrophils that infiltrate through the brain vascular vessel may affect the immune function of microglia in the brain, close investigation of the interaction between these cells is important in understanding neuroinflammatory phenomena and immunological aftermaths that follow. This study aimed to observe how the morphology and function of neutrophils and microglia are converted in the inflamed brain. To directly investigate cellular responses of neutrophils and microglia, LysMGFP/+ and CX3CR1GFP/+ mice were used for the observation of neutrophils and microglia, respectively. In addition, low-dose lipopolysaccharide (LPS) was utilized to induce acute inflammation in the central nervous system (CNS) of mice. Real-time observation on mice brain undergoing neuroinflammation via two-photon intravital microscopy revealed various changes in neutrophils and microglia; namely, neutrophil infiltration and movement within the brain tissue increased, while microglia displayed morphological changes suggesting an activated state. Furthermore, neutrophils seemed to not only actively interact with microglial processes but also exhibit reverse transendothelial migration (rTEM) back to the bloodstream. Thus, it may be postulated that, through crosstalk with neutrophils, macrophages are primed to initiate a neuroinflammatory immune response; also, during pathogenic events in the brain, neutrophils that engage in rTEM may deliver proinflammatory signals to peripheral organs outside the brain. Taken together, these results both show that neuroinflammation results in significant alterations in neutrophils and microglia and lay the pavement for further studies on the molecular mechanisms behind such changes.